Pembinaan Karakter Peserta Didik SMPN 3 Nusawungu Terhadap Mitigasi Bencana dan Kearifan Lokal - Idah Rahmayanti; Suwarno Suwarno (UM Purwokerto Press, 2022)
Character building of students towards Disaster Mitigation and Local Wisdom,An event can be said to be a disaster if it is the general public who are affected by the nature of which disturbs the safety and comfort of many people. Everyone must have the ability to prevent the impact of risks from disaster events. especially for selected people who have the main task and function for disaster management. they must be able and make efforts to prevent or reduce the impact of disasters starting from the ability to educate the public, evacuation and rescue, as well as reducing risks that have the potential to cause disasters. Three abilities that must be possessed by disaster management supervisors are broad knowledge, excellent physical, and good mentality. To support humanitarian work. I as an educator carry out coaching starting from physical development, science, and character building in order to train self-discipline to have a good attitude and never give up. This type of research uses qualitative research with data collection, observation and interview techniques. In this research,is a new thing that is a shared responsibility to protect the environment and has a high concern and is also participatory to all school members. This research also uses a qualitative approach with interview, observation and documentation data collection techniques. Implementation of Disaster Mitigation Character Development at SMPN 3 Nusawungu can be observed based on the objectives of the work program as program indicators. Factors that influence the achievement of disaster mitigation character building are facilitation, participation of school residents and school finances.